#### Answer

- Horizontal asymptote: $y=0$
- Vertical asymptote: $x=3$
As $x\to\pm\infty$, the dominant term is $0$.
As $x\to3$, the dominant term is $-3/(x-3)$.

#### Work Step by Step

$$y=\frac{-3}{x-3}$$
We are interested in the behavior of function $y$ as $x\to\pm\infty$ as well as the behavior of $y$ as $x\to3$, which is where the denominator is $0$.
We can rewrite the function into a polynomial with a remainder as follows: $$y=\frac{-3}{x-3}=0+\frac{-3}{x-3}$$
- As $x\to\pm\infty$, $(x-3)$ approaches $\pm\infty$ as well and $-3/(x-3)$ gets closer to $0$, meaning that the curve will approach the line $y=0$, which is also the horizontal asymptote.
One more thing, because $-3/(x-3)$ becomes closer to $0$, we can say the dominant term is $0$ as $x\to\pm\infty$.
- As $x\to3$, $(x-3)$ will approach $0$ and $-3/(x-3)$ will approach $-\infty$, meaning that the curve will approach $-\infty$ as well. So $x=3$ is the vertical asymptote.
And since $-3/(x-3)$ approaches $-\infty$ as $x\to3$, the dominant term is $-3/(x-3)$.
The graph is shown below. The red curve is the graph of $y=-3/(x-3)$, while the blue line is the horizontal asymptote $y=0$ and the green one is the vertical asymptote $x=3$.